Cascading guided search cloud service search engine - Arvaree@Alvar, Thamilvaani; Atan, Rodziah (IJCT Foundation, 2013)
Cloud computing is one contemporary technology in which the research community has recently embarked. This paradigm shifts the location of the infrastructure to the network to reduce the costs associated with the management of hardware and software resources. Developers with innovative ideas for new Internet services no longer require the large capital outlays in hardware to deploy their service or the human expense to operate it.Organization adopts cloud computing services through service provider via Internet .In recent years, numbers of cloud service providers are increase. However,there is no study that focuses on search engine and web portal for cloud computing for users who want to find cloud service. At the same time, “vendor lock in” issues and the lack of common cloud standards delayed the interoperability across these providers. Thus, lead the cloud customer to face challenges and problems in selecting the right service provider who meets their needs. This research focus on meeting the user requirement in cloud environment whereby, user requirements reflect to search query that entered by the end users and how these search queries are exactly matched with accurate cloud service. Therefore, end of the research cloud service search engine was developed a s a proposed tool for meeting the user requirements.